ANALISIS KEMAMPUAN KOMUNIKASI MATEMATIS SISWA PADA MATERI PROGRAM LINEAR - Handayani, Restu (Jurnal Edukasi dan Penelitian Matematika, 2023)
The purpose of this research is to find out the level of students' mathematical communication abilities. The type of research used is qualitative research with a descriptive approach. The stages in this study were divided into the preparation, implementation and analysis stage. The instrument used is a test in the form of essay questions which contain indicators of mathematical communication ability. This research was conducted in class XI IPS MAN 2 Kota Padang. The results showed that the level of mathematical ability in class XI IPS 2 MAN 2 Padang City was low especially in Linear Program material, which is caused by a lack of understanding related to Linear Program.Keywords: Analysis of Student’s Mathematical Ability, Communication Mathematical Ablitiy, Linear Program